2004
DOI: 10.2134/agronj2004.0800
|View full text |Cite
|
Sign up to set email alerts
|

Soybean Yield as Affected by Biomass and Nitrogen Uptake of Cereal Rye in Winter Cover Crop Rotations

Abstract: because of its winter-hardiness and its exceptional ability to scavenge residual N (Wagger and Mengel, 1988; The inclusion of cereal rye (Secale cereale L.) as winter cover crop Ditsch and Alley, 1991;Shipley et al., 1992; Bollero and (WCC) following corn (Zea mays L.) has been suggested as a valuable nutrient management tool in the typical corn-soybean [Glycine max Bullock, 1994). In a review paper, Meisinger et al. (1991) (L.) Merr.] rotation of the U.S. Midwest. However, little information reported re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
84
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(97 citation statements)
references
References 34 publications
12
84
1
Order By: Relevance
“…Also for Illinois andunder no-till, Villamil et al (2006, 2008) found that after three cycles of corn-soybean production with and without CCs, CC mixtures of cereal rye and hairy vetch drilled onto crop stubble each year increased SOM, nutrient retention, and water aggregate stability compared with winter fallow (no CC). Again, no effect on cash crop yields was detected in these systems for either corn (Miguez and Bollero, 2006) or soybean (Ruffo et al, 2004). According to the cover crop surveys performed every year since 2012 by the Conservation Technology Information Center (CTIC-SARE, 2016) however, farmers that have adopted CCs consistently report positive effects on crop yields and soil fertility in the Midwest region.…”
mentioning
confidence: 98%
“…Also for Illinois andunder no-till, Villamil et al (2006, 2008) found that after three cycles of corn-soybean production with and without CCs, CC mixtures of cereal rye and hairy vetch drilled onto crop stubble each year increased SOM, nutrient retention, and water aggregate stability compared with winter fallow (no CC). Again, no effect on cash crop yields was detected in these systems for either corn (Miguez and Bollero, 2006) or soybean (Ruffo et al, 2004). According to the cover crop surveys performed every year since 2012 by the Conservation Technology Information Center (CTIC-SARE, 2016) however, farmers that have adopted CCs consistently report positive effects on crop yields and soil fertility in the Midwest region.…”
mentioning
confidence: 98%
“…Winter adapted cereal cover crops tend to be more effective than legumes in NO 3 loss reduction in cold northern climates due to better fall and early spring growth (Shipley et al, 1992;Parkin et al, 2006), with RCC as a common cover crop choice (Ranells and Wagger, 1997;Ruffo et al, 2004;Kladivko et al, 2014). In addition, RCC has flexibility in establishment, relatively low seed cost, and winter hardiness (Feyereisen et al, 2006).…”
mentioning
confidence: 99%
“…However, applying N to RCC before control may offset potential yield decreases in corn ). Soybean yield is not usually affected by RCC because soybean is a legume, and not another cereal, like corn, following the RCC (Thelen and Leep, 2002;Ruffo et al, 2004;De Bruin et al, 2005;Hoorman et al, 2009). However, soybean yield decreases of 15 to 65% were reported with an RCC, part of the decrease associated with late RCC control in the spring and delay in soybean planting .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The inclusion of CC in a cropping sequence was not found to reduce soybean yield under unlimited water availability for crop production (Ruffo et al, 2004;Restovich et al, 2012). However, Singer & Kohler (2005) reported reductions in soybean yield and shoot biomass accumulation with the use of rye (Secale cereale L.) as CC in Iowa (USA).…”
Section: Grain Yieldmentioning
confidence: 99%